THE PURPOSE OF CURRENT HISTORICAL EDUCATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The beginning of the 21st century brought great changes to the education system. Globalization, technological development and access to information have a significant impact on the content and methods of school education, including history lessons. This article examines the features, problems and prospects of school history education at the beginning of the 21st century. History lessons are important for preserving the cultural heritage of a society, developing students’ critical thinking and understanding the roots of their nation. In the 21st century, history education makes a major contribution to the development of intercultural understanding, shaping global perspectives. Through history, students form views on their culture, national and universal values. They learn to look critically at historical events and analyze their causes and consequences.
Keywords: school, education, student, history, thinking, lessons, education